Over-The-Top Media in Digital Economy and Society 5.0 - Ramli, Tasya Safiranita; Ramli, Ahmad M; Adolf, Huala; Damian, Eddy; Palar, Miranda Risang Ayu (Journal of Telecommunications and the Digital Economy, 2020)
Indonesia has entered global economic development based on innovation, technology and knowledge. This is the first point where it becomes the driving force in economic growth. In this, in Indonesia there is a population of millennials who have new creativity and innovation that makes the potential that can increase economic growth based on the digital economy and pursue the Society 5.0.. Nowadays, innovation and creativity are the key to success in economic development in the era of globalization. It is also closely related to the intellectual property system. In the era of globalization, developed countries are those who are able to utilize intellectual property as a driving force for the economy through new science, technology, creativity and innovation. One of the changes in the media is Over The Top (OTT), which is quite popular either in the world of telecommunications, world governance or academic world. In the digital era, some companies implemented a system that will change the company’s digital revolution. Some companies need to restructuring their type of business based on digitalisation.